Field‐evolved resistance to insecticides in the invasive western flower thrips Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) in China. Issue 7 (4th January 2016) - Wang, Ze‐Hua; Gong, Ya‐Jun; Jin, Gui‐Hua; Li, Bing‐Yan; Chen, Jin‐Cui; Kang, Zong‐Jiang; Zhu, Liang; Gao, Yu‐Lin; Reitz, Stuart; Wei, Shu‐Jun
Abstract: BACKGROUND: To understand the current status of insecticide resistance of the invasive western flower thrips, Frankliniella occidentalis, in China, the responses of six field populations to six commonly used insecticides, i.e. spinosad, spinetoram, cyantraniliprole, imidacloprid, acetamiprid and pyriproxyfen, were evaluated in comparison with a susceptible laboratory strain. RESULTS: Field populations tended to be less susceptible than the laboratory strain. The population from Shouguang, Shandong Province, showed the lowest levels of susceptibility. A 15.64‐fold and 17.29‐fold resistance to spinosad and spinetoram was detected in the Shouguang population. A 11.74‐fold and 13.64‐fold resistance to cyantraniliprole was detected in populations from Daxing in the Beijing area and Shouguang. All populations showed a low level of resistance to imidacloprid, acetamiprid and pyriproxyfen, except for the Shouguang population, which was 127.58‐fold more resistant to pyriproxyfen. CONCLUSION: Variations in resistance to the tested insecticides were observed among the sampled population. Spinosad and spinetoram were the most efficient insecticides and are recommended for use in an integrated management programme. Resistance management strategies should be implemented to reduce the potential for resistance evolving. © 2015 Society of Chemical Industry